Mesopotamia’s Cylindrical Seals and their Intellectual and Aesthetic Dimensions A Study of Ancient History - Shaalan Rahm , Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The first beginnings of the use of seals date back to the Neolithic period around 8000 B.C. in Iraq, Syria, and Anatolia. Clay seals with a handle were sometimes found in a tablet hill made of white chalky gypsum, whose inscriptions were simple, including single-center circles, continuous rectangles, and mesh-adorned motifs, and discoveries at the sites of Tal Al-Abeba in Wadi Al-Bligh, north of the Syrian city of Raqqa, and in Tel Arbashia St. Mosul promoted the early management during the fifth millennium B.C., stamping seals over clay blocks that had formed around the thread knot in order to protect goods, and those early seals were characterized by a simple geometric formation and far from complexity and a schematic style, and almost converging other arts that characterized with the same advantage.